Self‐Powered Frequency‐Selective Acoustic Sensor Based on Bound States in the Continuum - Chao Song; Sibo Huang; Hongyu Ma; Shuhuan Xie; Din Ping Tsai; Jie Zhu; Yong Li (Advanced Science)
Abstract Sound is a clean, renewable, and abundant energy source present ubiquitously in nature. However, it is often underutilized due to its low energy density in most environments. This study introduces a two‐state system that supports a Friedrich–Wintgen bound state in the continuum (BIC), achieving an unprecedented enhancement in sound energy density—up to 1849 times the incident sound intensity. By integrating this BIC‐supporting system with energy conversion mechanisms, such as piezoelectric films, high‐performance acoustic energy harvesting and sensing is realized. As a proof‐of‐concept, a self‐powered acoustic sensor system is developed. This sensor leverages the high‐quality‐factor nature of a BIC, providing exceptional passive frequency selectivity and the ability to activate a light‐emitting diode (LED) at the target frequency of 501 Hz with an offset of only 4 Hz. This work represents a groundbreaking advancement in sound‐energy enhancement, paving the way for BIC‐induced acoustic harvesters and sensors, with promising applications in wireless sensor networks and the Internet of Things.